Enhanced Circularly Polarized Luminescence in Emissive Charge‐Transfer Complexes. Issue 21 (15th April 2019) - Han, Jianlei; Yang, Dong; Jin, Xue; Jiang, Yuqian; Liu, Minghua; Duan, Pengfei
Abstract: Achieving a large dissymmetry factor ( g lum ) is a challenge in the field of circularly polarized luminescence (CPL). A chiral charge‐transfer (CT) system consisting of chiral electron donor and achiral electron acceptor shows bright circularly polarized emission with large g lum value. The chiral emissive CT complexes could be fabricated through various approaches, such as grinding, crystallization, spin coating, and gelatinization, by simply blending chiral donor and achiral acceptor. The structural synergy originating from π–π stacking and strong CT interactions resulted in the long‐range ordered self‐assembly, enabling the formation of supramolecular gels. Benefiting from the large magnetic dipole transition moment in the CT state, the CPL activity of CT complexes exhibited large circular polarization. Our design strategy of the chiral emissive CT complexes is expected to help the development of new molecular engineering strategies for designing highly efficient CPL‐active materials. Abstract : Circularly polarized luminescence of charge‐transfer complexes was demonstrated for the first time. The complexes feature a large g lum value owing to charge‐transfer interactions. Benefiting from the large magnetic dipole transition moment in the charge‐transfer state, the CPL activity of mixed‐stack CT complexes exhibited large circular polarization.